ESTIMASI BIOMASSA DAN CADANGAN KARBON PADA TINGKAT SEMAI RHIZOPHORA MUCRONATA DI DESA SEPATIN SEBAGAI KAWASAN RESTORASI MANGROVE - Widia Sri Utami; Oshlifin Rucmana Saud; Ulfiah Nurhikmah; Anggy Riskha Putri Setyadi (UNIVERSITAS NEGERI MAKASSAR, 2025)
Land conversion of mangrove ecosystems in Sepatin Village, which is part of an active coastal area, is currently facing significant ecological pressures. One of the main factors leading to the destruction of mangrove forests is the development of aquaculture ponds, which is carried out massively to meet global market demand. The purpose of this study was to estimate the carbon uptake of Rhizophora mucronata seedlings in mangrove restoration areas. The method used was purposive sampling method by making 5 sample plots of 2 m x 2 m square size for seedling level. Data analysis used allometric model I, namely Y = 35.013 x Base diameter1.860 and Model II, namely Y = 0.251 x (Base diameter2H)0.954 to estimate carbon stocks at the seedling level. Model I uses base diameter as independent variable while model II uses base diameter and seedling height as independent variables. The results showed that the estimated biomass and carbon stocks at the seedling level were 20.08 kg and 12.14 kg, while the biomass was 9.4 kg and 4.43 kg.